Tren Riset Global Metabolit Sekunder Bekatul Beras Hitam dan Aktivitas Farmakologisnya: Tinjauan Bibliometrik (1992–2025) - I Gusti Yogaswara; Lalu Husnul Hidayat; Navista Sri Octa Ujiantari; Soni Siswanto (Jurnal Penelitian Pendidikan IPA, 2026)
Black rice bran is an agricultural by-product rich in secondary metabolites with potential pharmacological activities, particularly antioxidant and antidiabetic effects. Despite increasing research on its bioactive compounds, the development of research trends and collaboration patterns in this field has not been systematically analyzed. This study aims to evaluate global research trends on the secondary metabolites and pharmacological activities of black rice bran using a bibliometric approach. Bibliographic data were retrieved from the Scopus database and selected using the PRISMA 2020 framework. The dataset was cleaned using OpenRefine and analyzed using the Bibliometrix R-package via the Biblioshiny interface, while network visualization was performed using VOSviewer. The results show a gradual increase in publications, particularly after 2018, with research mainly published in journals related to food chemistry and functional foods. Institutional contributions are largely dominated by Southeast Asian universities, especially in Thailand. Thematic evolution indicates a shift from phytochemical characterization toward pharmacological investigations, particularly antioxidant and antidiabetic activities. These findings highlight the growing scientific interest and potential of black rice bran as a promising natural resource for health promotion.